Compressive behaviour and capacities of S690 high strength steel welded π-shaped and cruciform section stub columns - Chen, Qianzhi (2024)
This paper reports experimental and numerical investigations into the cross-sectional behaviour and resistances of S690 high strength steel welded π-shaped and cruciform section stub columns under compression. An experimental investigation was firstly carried out on five S690 high strength steel welded π-shaped sections and five S690 high strength steel welded cruciform sections (covering both non-slender and slender sections) and included material tensile coupon tests, initial local geometric imperfection measurements and twenty stub column tests. The experimental investigation was supplemented by a numerical modelling investigation, where finite element models were firstly developed to simulate test structural responses and subsequently adopted to conduct parametric studies to generate further numerical data. On the basis of the obtained experimental and numerical data, the relevant design rules for high strength steel welded sections under compression, as set out in the European code, American specification and Australian standard, were assessed. The assessment results indicated that (i) the European code and American specification led to overall accurate and consistent cross-section compression resistance predictions for S690 high strength steel welded π-shaped sections, but provided slightly conservative and scattered resistance predictions for their cruciform section counterparts, and (ii) the Australian standard was accurate and consistent when used for non-slender S690 high strength steel welded π-shaped sections, but the design resistances were conservative and scattered for slender S690 high strength steel welded π-shaped sections as well as non-slender and slender S690 high strength steel welded cruciform sections.